2007
DOI: 10.1158/1078-0432.ccr-06-2377
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Phase II Study of Two Doses of Pemetrexed as First-Line Chemotherapy for Advanced Breast Cancer

Abstract: Purpose: Pemetrexed has shown varied response rates in advanced breast cancer. This randomized, double-blind, phase II study was conducted to assess the efficacy and safety of two doses of pemetrexed in a homogeneous population. A secondary objective was to identify molecular biomarkers correlating with response and toxicity. Experimental Design: Patients with newly diagnosed metastatic breast cancer or locally recurrent breast cancer received 600 mg/m 2 (P600 arm) or 900 mg/m 2 (P900 arm) of pemetrexed on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…Another patient who received 900 mg/m 2 developed renal failure that resolved 13 days after cessation of the drug. 6 In another phase III trial, in 121 fully vitaminsupplemented patients who received pemetrexed (500 mg/m 2 ), 2 patients experienced grade 1 and 2 (reversible) decrease in creatinine clearance. 7 Since most of the trials had excluded patients with baseline creatinine clearance of <60 mL/min because of increased toxicity, little is known about the potential nephrotoxic effects of pemetrexed at a lower level of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Another patient who received 900 mg/m 2 developed renal failure that resolved 13 days after cessation of the drug. 6 In another phase III trial, in 121 fully vitaminsupplemented patients who received pemetrexed (500 mg/m 2 ), 2 patients experienced grade 1 and 2 (reversible) decrease in creatinine clearance. 7 Since most of the trials had excluded patients with baseline creatinine clearance of <60 mL/min because of increased toxicity, little is known about the potential nephrotoxic effects of pemetrexed at a lower level of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In our study of dose-dense, single-agent pemetrexed given as first-line treatment to women with MBC, we observed an ORR of 26% (CR 3%, PR 23%) and 40% CBR. Llombart-Cussac and colleagues observed response rates of 17 and 19% when pemetrexed was given at 600 and 900 mg/m 2 to MBC patients in the first-line setting on Day 1 of a 21-day cycle [25]. Earlier 21-day trials have shown response rates in anthracyclinerefractory groups (ORR 17%), anthracycline-failure groups (ORR 24%), anthracycline-and taxane-pretreated groups (ORR 26% and ORR 28%, respectively), and heavily pretreated groups who had received prior anthracycline, a taxane, and capecitabine (ORR 8%) [15,17,26].…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II trial where advanced metastatic breast cancer patients received 600 or 900 mg/m 2 pemetrexed as a first-line treatment, pemetrexed produced moderate antitumor activity, with response rate at 16% and a clinical benefit at approximately 40% [16]. In two phase II studies, where advanced colorectal cancer patients received pemetrexed at 600 or 500 mg/m 2 as firstline treatment, objective response rates were 15.4% and 17.2%, respectively [17].…”
Section: Discussionmentioning
confidence: 99%